ACE Inhibitory Properties and Phenolics Profile of Fermented Flours and of Baked and Digested Biscuits from Buckwheat - Zieliński, Henryk (Foods, 2020)
The angiotensin converting enzyme (ACE) inhibitory activity and phenolics profile of fermented flours and of baked and digested buckwheat biscuits was studied. The fermentation of buckwheat flour by select lactic acid bacteria (LAB) caused a decrease in ACE inhibitory activity as compared to the non-fermented flour. The baking process significantly reduced the ACE inhibitory activity of biscuits obtained from fermented flours, whereas digestion significantly increased these properties. In non-fermented and fermented flours and buckwheat biscuits before and after in vitro digestion samples, ten phenolic acids and eight flavonoids were found. Highly significant correlations were found between sample concentration of 50% inhibition of ACE (IC(50)) and total phenolic compounds of fermented flour and biscuits before and after digestion for each applied LAB, thus indicating a link between phenolic compound content and ACE inhibitory activity. In the digested biscuits, the input to ACE inhibitory activity was provided by p-coumaric, sinapic, syringic, vanillic, and protocatechuic acids as well as by kaempherol, quercetin, apigenin, and orientin. Therefore, it can be concluded that cumulative action of those phenolic acids and flavonoids released after digestion is responsible, in part, for the bioaccessible ACE inhibitory activity of buckwheat biscuits.